2006
DOI: 10.1093/jac/dkl382
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal activity of five cathelicidin peptides against clinically isolated yeasts

Abstract: This study indicates that these five structurally varied host defence peptides are all endowed with the capacity to inactivate a number of fungal pathogens, irrespectively of their resistance to antifungal drugs, and suggests they might be potentially useful leads for the development of novel fungicidal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 44 publications
7
92
0
1
Order By: Relevance
“…The antifungal activity of LL-37 and BMAP-28 has been reported previously (22,27). The activity of all five peptides was examined against two agronomically important fungal pathogens, F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 85%
“…The antifungal activity of LL-37 and BMAP-28 has been reported previously (22,27). The activity of all five peptides was examined against two agronomically important fungal pathogens, F. oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 85%
“…However, C. glabrata has been shown to be scarcely susceptible to a wide spectrum of AMPs of different derivations; among these are histatin, cathelicidins, defensins, and magainin (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Numerous studies have suggested that naturally occurring host defense peptides (30)(31)(32)(33)(34) and synthetic derivatives of these peptides (35-37) could be useful drugs to treat fungal infections, including those caused by Candida pathogens. Since Candida spp.…”
Section: Discussionmentioning
confidence: 99%